SHIP® With a client experiencing Meige’s Syndrome : a Hermeneutic Single-Case Efficacy Study - Macklin, Daleen (University of Pretoria, 2018)
Mini Dissertation (MA Clinical Psychology)--University of Pretoria, 2018.